Karakteristik Petani Dalam Pengembangan Hutan Rakyat Di Desa Buana Sakti Kecamatan Batanghari Kabupaten Lampung Timur - Resti Widya Putri; Rommy Qurniati; Rudi Hilmanto (Jurnal Sylva Lestari, 2015)
Effort to conserve forest as one source of food for farmers is organized by developing a community forest. This effort is carried by culture various types of forestry, agriculture, and livestock. To encourage the development of community forest, it is necessary to investigate the farmers characteristics who worked in the forest. The purpose of this study is to describe the characteristics and income level of farmers in developing community forests. The study was conducted in  March 2014 in the Village of Buana Sakti. The formal education of fifty percent (50%) of farmers in Buana Sakti Village were up to elementary school, while for their informal education are less active in extention activities, talks, and workshops. The availability of credit in Buana Sakti Village come from two sources: Village cooperative (KUD) and BRI bank. Buana Sakti Village has three shops of input. The income of private forest farmers in Buana Sakti Village comes from forest trees product, agriculture crops, livestock, and other work (civil servants, laborers, merchants, artisans, village chief). The average farmers income are Rp 25,286,960 each year, while for the interaction farmers in Buana Sakti Village has a strong interaction with each other. Farmers should be more active to participate in extension activities, talks, and workshops conducted by the extension workers or the relevant agencies so that the knowledge and information obtained will be more and more analysis on the characteristics of farmers is needed in developing community forest to inprove forest sustainability. Keywords: Buana Sakti, characteristics, community forests, farmer